2019
DOI: 10.1038/s41598-018-38435-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-302a inhibits human HepG2 and SMMC-7721 cells proliferation and promotes apoptosis by targeting MAP3K2 and PBX3

Abstract: Hepatocellular carcinoma (HCC) is the most common liver cancer and has a poor prognosis. miR-302a is an important regulator of tumor occurrence and deterioration, while MAP3K2 and PBX3 genes are involved in cancer cell proliferation and apoptosis. In this study, the expression of miR-302a and MAP3K2/PBX3 were evaluated by qPCR in liver cancer cell lines. Next, the target relationship between miR-302a and MAP3K2/PBX3 was verified using luciferase assays. Meanwhile, the expression correlation between miR-302a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…HCC is one of the most prevalent malignancies and the leading cause of cancer-related deaths worldwide ( Wang et al, 2019 ). Local recurrence and distant metastasis often result in poor prognosis ( Ringehan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCC is one of the most prevalent malignancies and the leading cause of cancer-related deaths worldwide ( Wang et al, 2019 ). Local recurrence and distant metastasis often result in poor prognosis ( Ringehan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are abnormally expressed in tumors and play a role either as oncogenes or tumor suppressor genes in tumor progression. 14 Some studies have compared nine gastric cancer cell lines detected by the miRNAs microarray with normal gastric tissues, and miR-126 was significantly downregulated. 15 Yue et al also found that miR-126 expression in gastric cancer tissues decreased significantly, and in vitro gastric cancer cells could inhibit the growth of SGC7901 cells by inducing the G0/G1 phase to block the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that an additional miR, miR-320a, can be transferred to HCC cells from neighboring cancer-associated fibroblasts (CAFs) via exosomes. Once in HCC cells, miR-320a can block proliferation and migration through inhibition of EMT, as well as cyclin-dependent kinase 2 (CDK2) and MMP2 [27], and (from a later study) MAP3K2 [34].…”
Section: Liver Cancermentioning
confidence: 96%
“…The first report of a PBX3-specific miR was published in 2011, when Ramberg et al demonstrated that the miR-let-7d repressed PBX3 expression in prostate cancer [14], and this was followed shortly after by a report that the closely related miR-let-7c was complementary to the 3'UTR of PBX3 and could directly repress its expression in colorectal cancer [17], as could miR-let-7b in glioma [18]. Subsequently, PBX3 expression was also shown to be reduced by miR-181 in AML [19], miR-129-5p in pancreatic cancer [20], miR-495 in AML [21] and melanoma [22], miR-200b in breast cancer [23], miR-200b, miR-222, and miR-424 in hepatocellular carcinoma (HCC) [24], miR-320a in multiple myeloma [25], gastric cancer [26], and cancer-associated fibroblasts (CAFs) associated with HCC [27], miR-33a-3p in HCC [28], miR-497 in multiple myeloma [29], miR-144-3p in gastric cancer [30], miR-98 in glioma [31], miR-144 in lung cancer [32] and HCC [33], miR-302a in HCC [34], and miR-526b in cervical cancer [35]. In addition, within the context of early development, miR-320 was shown to maintain the undifferentiated state in chick blastodermal cells through repression of PBX3 [5].…”
Section: Transcriptional and Post-transcriptional Regulation Of Pbx3mentioning
confidence: 99%
See 1 more Smart Citation